2009
DOI: 10.1136/jnnp.2009.186239
|View full text |Cite
|
Sign up to set email alerts
|

Use of drugs with anticholinergic effect and impact on cognition in Parkinson's disease: a cohort study

Abstract: Our findings suggest that there is an association between anticholinergic drug use and cognitive decline in PD. This may provide an important opportunity for clinicians to avoid increasing progression of cognitive decline by avoiding drugs with AA. Increased awareness by clinicians is required about the classes of drugs that have anticholinergic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(174 citation statements)
references
References 41 publications
7
165
0
2
Order By: Relevance
“…With the role played by the striatal interneurons in the development of motor symptoms, anticholinergic drugs were one of the original treatments for Parkinson's disease; indeed they are still used as an adjunct treatment to the dopamine precursor, levadopa, because they ameliorate the movement disorder associated with the disease [123]. However, due to their nonspecific nature these drugs have a number of side effects-including exacerbation of cognitive decline [123].…”
Section: Muscarinic Receptors and Parkinson's Diseasementioning
confidence: 99%
“…With the role played by the striatal interneurons in the development of motor symptoms, anticholinergic drugs were one of the original treatments for Parkinson's disease; indeed they are still used as an adjunct treatment to the dopamine precursor, levadopa, because they ameliorate the movement disorder associated with the disease [123]. However, due to their nonspecific nature these drugs have a number of side effects-including exacerbation of cognitive decline [123].…”
Section: Muscarinic Receptors and Parkinson's Diseasementioning
confidence: 99%
“…Regression analysis adjusting for age, depression and baseline cognition suggested that duration and load of anti-cholinergic drugs were both significantly associated with decline on MMSE score. 68 Conversely, cholinesterase inhibitors (ChEIs) -drugs that indirectly increase the availability of ACh -are the only proven treatment to enhance cognitive function in PDD according to meta-analysis. 69 …”
Section: Acetylcholinementioning
confidence: 99%
“…We obtained data on drugs published in anticholinergic rating scales from seven articles [7][8][9][10][11][12][13] used in a systematic review [3] that evaluated the differences between each anticholinergic rating scale and the relation between anticholinergic burden and adverse effects. In these articles, drugs were ranked by the strength of their anticholinergic effects.…”
Section: Drugs Used In the Decision Tree And Their Anticholinergic Ementioning
confidence: 99%
“…In total, we obtained 545 drugs from seven articles [7][8][9][10][11][12][13]. Bismuth subsalicylate was excluded due to the many missing values in its calculated descriptors.…”
Section: Drugs and Descriptorsmentioning
confidence: 99%